Vinylene-Linked Two-Dimensional Covalent Organic Frameworks: Synthesis and Functions - Xu, Shunqi; Richter, Marcus; Feng, Xinliang (Accounts of Materials Research, 2021)
ConspectusTwo-dimensional covalent organic frameworks (2D COFs) with covalently bonded repeat units and crystalline, porous framework backbones have attracted immense attention since the first 2D COFs were reported by Yaghi's group in 2005. The extended single-layer structures of 2D COFs are also generally considered to be the 2D polymers. The precise incorporation of molecular building blocks into ordered frameworks enables the synthesis of novel organic materials with designable and predictable properties for specific applications, such as in optoelectronics, energy storage, and conversion. In particular, the 2D π-conjugated COFs (2D-c-COFs) represent a unique class of 2D conjugated polymers that have 2D molecular-periodic structures with extended in-plane π-conjugations. In the 2D-c-COFs, the conjugated skeletons and π-πstacking interactions can provide the pathways for electron transport, while the porous channel can enable the loading of active sites for catalysis and sensing. Thus far, the synthesis of 2D-c-COFs has been mostly limited to Schiff base chemistry based on the condensation reaction between amine and aldehyde/ketone monomers because the construction of 2D COFs as thermodynamically controlled products generally requires a highly reversible reaction for error-correction processes. However, the high reversibility of imine linkages would conversely endow moderate π-electron delocalization due to the polarized carbon-nitrogen bonds and poor stability against strong acids/bases.To achieve robust and highly conjugated 2D-c-COFs, a series of synthesis strategies have been developed, including a one-step reversible reaction with a bond-forming-bond braking-bond reforming function, a quasi-reversible reaction combing reversible and irreversible processes, and postmodifications converting labile bonds to a robust linkage. Among all of the reported 2D-c-COFs, vinylene-linked (also sp2-carbon-linked) 2D covalent organic frameworks (V-2D-COFs) with high in-plane π-conjugation have attracted increasing interest after we reported the first V-2D-COFs via a Knoevenagel polycondensation in 2016. Although C=C bonds have low reversibility, making the synthesis of V-2D-COFs quite challenging, there have been around 40 V-2D-COFs reported over the past 5 years, which demonstrated the merits of V-2D-COFs combining with unique optoelectronic, redox, and magnetic properties.In this Account, we will summarize the development of V-2D-COFs, covering the important aspects of synthesis methods, design strategies, unique physical properties, and functions. First, the solvothermal synthesis of V-2D-COFs using different reaction methodologies and design principles will be presented, including Knoevenagel polycondensation, other aldol-type polycondensations, and Horner-Wadsworth-Emmons (HWE) polycondensation. Second, we will discuss the optoelectronic and magnetic properties of V-2D-COFs. Finally, the promising applications of V-2D-COF in the fields of sensing, photocatalysis, energy storage, and conversion will be demonstrated, which benefit from their robust vinylene-linked skeleton, full in-plane π-conjugation, and tailorable structures. We anticipate that this Account will provide an intensive understanding of the synthesis of V-2D-COFs and inspire the further development of this emerging class of conjugated organic crystalline materials with unique physicochemical properties and applications across different areas.
CRIS-Team Scopus Importer:2023-03-20